Proposta e avaliação de uma política pública contra a desigualdade econômica no Brasil: a sociedade de participantes - Pinto, Sergio Luiz de Moraes (2006)
This dissertation proposes and evaluates ex-ante a public policy, the Stakeholder Society, looking for reduce the economic inequality in Brazil. First, it discusses the effects of economic inequality in a country social tissue and in the economic growth. Second, the basic concepts of distributional justice are discussed; comparing the ideals from the right libertarianism and the left egalitarianism, and asserting that the public policy proposed meets both ideals. Following this theoretical discussion, different inequality measures are presented, including an entirely novel methodology that allows capturing in fine detail the contribution to inequality of the changing position of every major economic sector and every geographic region. The ethical inequality measures are also explained and applied to Brazil. The dissertation then discusses the Stakeholder Society proposal. It is compared to similar public policy debated and adopted in other countries and to the basic income proposal. The dissertation also dialogue with the basic capital critics in the present political science literature. The next step is to explain demographic concepts used to evaluate the public policy proposal. Microsimulation modeling is employed in the analysis, and its main ideas are also debated. The Brazilian tax structure is based in a regressive indirect taxation, and, to implement the Stakeholder Society, a new structure with a wealth tax is proposed. The wealth tax is also detailed in the study. The results of the public policy proposal are simulated between 2008 and 2080. They suggest that the Stakeholder Society would be very efficient to reduce inequality and finish endemic poverty in Brazil.